2011
DOI: 10.1016/j.mee.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field polarization and temperature on the effective permittivity and conductivity of porous anodic aluminium oxide membranes

Abstract: Porous insulators offer new opportunities for the controlled guest–host synthesis of nanowires for future integrated circuits characterized by low propagation delay, crosstalk and power consumption. We propose a method to estimate the effect of the electric field polarization and temperature on the electrical properties of different types of synthesized porous anodic aluminium oxide membranes. It results that the effective permittivity along the pore axis is generally 20% higher than the one in the orthogonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…So, the increase of the electrolyte temperature increases the dissolution rate and leads to the formation of wider pores [19]. Also, the pore densities of this study are close to the values obtained under similar operating conditions and presented in other works [20,21].…”
Section: Influence Of the Temperaturesupporting
confidence: 89%
“…So, the increase of the electrolyte temperature increases the dissolution rate and leads to the formation of wider pores [19]. Also, the pore densities of this study are close to the values obtained under similar operating conditions and presented in other works [20,21].…”
Section: Influence Of the Temperaturesupporting
confidence: 89%
“…The most common anodization electrolytes are sulfuric, 15 oxalic, 16 and phosphoric acid. 17 Two main methods of anodization have been established, which are termed hard anodization (HA) and mild anodization (MA). Anodization in oxalic acid has gained importance due to its capability to produce a large variety of pore diameters and film thicknesses, depending on the anodization voltage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The mechanical and optical properties of AAO depend on the anodization conditions, i.e., voltage and the type of electrolyte used. The most common anodization electrolytes are sulfuric, oxalic, and phosphoric acid . Two main methods of anodization have been established, which are termed hard anodization (HA) and mild anodization (MA).…”
Section: Introductionmentioning
confidence: 99%
“…An Analysis of the Electrolyte Resistivity Effect on the Pore Diameter and Pore Density of Anodic Aluminium Oxide (AAO) Films Produced by Single-step Anodization many researchers have worked on the porous AAO phenomenon on aluminum and its alloys. They have reported porous AAO formed on anodized aluminum with pore diameters in the range of 13273 nm and pore densities of 10 13 pores/cm 2 (Bartolomé et al, 2006;Gao et al, 2008;Tamburrano et al, 2011).…”
mentioning
confidence: 99%
“…The mechanism of porous AAO formation is still debated; previous reports have attributed it to the dynamic equilibrium of aluminum oxide formation and local field-assisted aluminum oxide dissolution (barrier layer dissolution; Vrublevsky et al, 2006;Sulka, 2008;Chung et al, 2011;Kikuchi et al, 2014). Many studies have shown that porous AAO morphology, such as pore diameter, pore wall thickness, porosity, interpore distance, and pore density, can be controlled simply by varying the anodizing parameters (Sulka & Parkoła 2007;Belwalkar et al, 2008;Chung et al, 2011;Tamburrano et al, 2011;Theohari & Kontogeorgou, 2013;Zaraska et al 2013). Temperature plays an important role during the anodizing process and significantly affects the morphology of porous AAO (Sulka & Parkoła, 2007;Theohari & Kontogeorgou, 2013).…”
mentioning
confidence: 99%